Universities Graduates in the Far East Labour Market - V. A. Gurtov; I. S. Stepus; S. S. Shabaeva (Moscow Polytechnic University, 2019)
High-skilled human resources constitute the basis of the Far Eastern regions' economy declared to be a national priority for the current century. The article discusses both graduates' employability indicators of the Far Eastern universities and post-education migration indicators within the Far Eastern Federal District and between other Russian regions. It is shown that despite negative migration indicators the Far Eastern regions are attractive for young university-trained professionals. A quantitative assessment of the Far Eastern educational institutions was performed based both on a comparative analysis of annual additional recruitment needs indicators in university-trained human resources as well as of university graduates' numbers employed in the Far East. It was revealed that annual shortage of university-trained human resources for the Far East amounts to 13,000 taking into account both graduates' employability and migration flows. Balance tables development such as "recruitment need - output" in terms of aggregated major groups/ fields of study contributed to carry out a qualitative analysis of the economy needs' provision for university graduates in the Far Eastern regions. Possible ways for the Far Eastern economy balancing in human resources were also identified including an increased volume of training high-skilled human resources up to a state level; promotion of graduates' migration from "non-Far Eastern" universities to Far Eastern Federal District; employer-sponsored education development in the interests of Far Eastern companies at Russian universities outside the Far Eastern Federal District. The article makes the case for the development of the information system for graduates, which promotes a positive image of Far East District as a geostrategic territory both for youth well-being and professional activities. The graduates should be aware of social, economic, and cultural prospects of the region's strategic development as a territory of advanced social and economic development, be clear on the advantages in case of their employment in Far Eastern region.